The Effects Of Synchronous And Asynchronous Mathematics Based Robotic Education In Primary Schools: Investigating Computational Thinking, Interest And Self-Efficacy Across Gender - Varaman, Parameshvaran (2024)
This study aimed to investigate the effects of synchronous and asynchronous virtual robotic education on primary school students’ perceived interest, self-efficacy, computational thinking (CT) skills and computational thinking (CT) achievement, while considering the moderating role of gender. As technology continues to advance, there remains a knowledge gap in understanding how synchronous and asynchronous modes of instruction influence computational thinking, interest, and self-efficacy across gender in primary school students. As for the significance, the unique use of educational robotics as a fundamental teaching method in STEM subjects not only brings additional educational benefits but also allows students to engage more with virtual ER, leading to increased interaction and accessibility from anywhere and anytime, ultimately helping to reduce the gender gap by involving and motivating girls to pursue future professions in STEM-related fields. Therefore, a 2x2 factorial design was employed quantitatively using quasi experimental design, with the independent variable (IV) consisting of two levels representing synchronous learning (SVRP) and asynchronous learning (AVRP), and gender serving as the moderator variable.